2012
DOI: 10.1093/cercor/bhs285
|View full text |Cite
|
Sign up to set email alerts
|

Decreased NOS1 Expression in the Anterior Cingulate Cortex in Depression

Abstract: Decreased function of the anterior cingulate cortex (ACC) is crucially involved in the pathogenesis of depression. A key role of nitric oxide (NO) has also been proposed. We aimed to determine the NO content in the cerebrospinal fluid (CSF) and the expression of NO synthase (NOS) isoforms, that is, NOS1, NOS2, and NOS3 in the ACC in depression. In depressive patients, CSF-NOx levels (the levels of the NO metabolites nitrite and nitrate) were significantly decreased (P = 0.007), indicating a more general decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 73 publications
2
48
0
2
Order By: Relevance
“…The findings are compatible with findings in rodents implicating NOS1 in behavioural, neural, and endocrine responses to stress (Zhou et al, 2011). In humans, post-mortem studies have shown altered NOS1 levels in the anterior cingulate cortex (Gao et al, 2013) and hippocampus (Oliveira et al 2008) of depressed patients compared with non-depressed individuals, and the NOS1 SNP rs6490121 has been associated with changes in prefrontal cortical function and grey matter density (Rose et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…The findings are compatible with findings in rodents implicating NOS1 in behavioural, neural, and endocrine responses to stress (Zhou et al, 2011). In humans, post-mortem studies have shown altered NOS1 levels in the anterior cingulate cortex (Gao et al, 2013) and hippocampus (Oliveira et al 2008) of depressed patients compared with non-depressed individuals, and the NOS1 SNP rs6490121 has been associated with changes in prefrontal cortical function and grey matter density (Rose et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…The hypothalamo-pituitary-adrenal (HPA)-axis, the monoamine systems and the autonomic nervous system are key regulating systems for stress responses and form major pathways for symptoms of depression [4,5]. Altered glutamatergic and reduced GABAergic and NO neurotransmission were observed in depression in a number of brain systems, which may significantly affect the neuronal activity involved in stress responses and mood regulation [1,2,6]. Changes in depression in the levels of these amino acids were found not only in different brain regions and cerebrospinal fluid (CSF), but also in blood and urine [7], which implies that they have the potential to serve as clinically relevant biomarkers or treatment efficacy monitors.…”
Section: Introductionmentioning
confidence: 99%
“…There is no difference between subjects; the frequencies are similar for controls and MDD patients [49]. In an autopsy and tissue bank-based study from Holland, there is decrease in nNOS expression in the anterior cingulate cortex of MDD-diagnosed people [50].…”
Section: Roles Of Noss In Neuropsychiatric Diseasesmentioning
confidence: 85%